Antimicrobial resistance profiles of Escherichia coli from swine farms using different antimicrobials and management systems - Ketkhao, Pramualchai (Vet World, 2021)
BACKGROUND AND AIM: The emerging of antimicrobial-resistant foodborne bacteria is a serious public health concern worldwide. This study was conducted to determine the association between farm management systems and antimicrobial resistance profiles of Escherichia coli isolated from conventional swine farms and natural farms. E. coli isolates were evaluated for the minimum inhibitory concentration (MIC) of 17 antimicrobials, extended-spectrum beta-lactamase (ESBL)-producing enzymes, and plasmid-mediated colistin-resistant genes. MATERIALS AND METHODS: Fecal swabs were longitudinally collected from healthy pigs at three stages comprising nursery pigs, fattening pigs, and finishers, in addition to their environments. High-generation antimicrobials, including carbapenem, were selected for the MIC test. DNA samples of colistin-resistant isolates were amplified for mcr-1 and mcr-2 genes. Farm management and antimicrobial applications were evaluated using questionnaires. RESULTS: The detection rate of ESBL-producing E. coli was 17%. The highest resistance rates were observed with trimethoprim/sulfamethoxazole (53.9%) and colistin (48.5%). All isolates were susceptible to carbapenem. Two large intensive farms that used colistin-supplemented feed showed the highest colistin resistance rates of 84.6% and 58.1%. Another intensive farm that did not use colistin showed a low colistin resistance rate of 14.3%. In contrast, a small natural farm that was free from antimicrobials showed a relatively high resistance rate of 41.8%. The majority of colistin-resistant isolates had MIC values of 8 mg/mL (49%) and ≥16 mg/mL (48%). The genes mcr-1 and mcr-2 were detected at rates of 64% and 38%, respectively, among the colistin-resistant E. coli. CONCLUSION: Commensal E. coli were relatively sensitive to the antimicrobials used for treating critical human infections. Colistin use was the primary driver for the occurrence of colistin resistance in swine farms having similar conventional management systems. In the natural farm, cross-contamination could just occur through the environment if farm biosecurity is not set up carefully, thus indicating the significance of farm biosecurity risk even in an antimicrobial-free farm.